A História local como um caminho para o ensino significativo de História nos anos iniciais - Teixeira, Olga Suely (2018)
Teaching History for students in the initial years (1st to 5th Years of Basic Education) is often understood as a task that presents no difficulties. However, in practice, this activity requires, from the teaching professional responsible for it, a high degree of reflection, since it is dealing with the formation of the citizen. Thus, and through observations made in the school environment, the present research appeared. There are several justifications for the development of a work in these ways, but I can highlight the fact that the majority of the research done in the Academic Masters will turn to the ways of teaching History and develop from the classrooms of the final years (6th to 9th Years) and / or high school. Here we prioritize the objectives of teaching and the classes in which the children establish the first contacts with this discipline, often determinant for the relation that will maintain with her during the life. In addition, the research proposes to give an answer based on objective data to the questions asked by the teachers of these classes on how to teach History in a less tedious way for them and their children. The objectives of this work were to investigate the teaching practices of History developed in these classrooms and to suggest strategies that favor the construction of historical knowledge from the elaboration of didactic material providing conditions to help the student to think historically. To try to answer the problem question - how to make the teaching-learning process significant in History in the initial years? - the hypothesis was that local history could be the object from which students could learn to think historically. The methodology initially counted on a bibliographical research; then the work of consultation and analysis of the sources (legal documents of the national education, politicalpedagogical project of the school field of research, questionnaires, lesson plans and field diaries) dialoguing with the theoretical-methodological references allowed to reach, since the discussion is still largely lacking in research, but inferences that point to directions and possibilities for teaching history in the early years. On the hypothesis of the use of local history, it is inferred that its use is effective when one wants to form a critical and active citizen, since it brings the children closer to their daily life and allows the school to systematize extra-mural experiences, demonstrating that the so-called historical events affect not only their locality but also connect to other contexts. To the proposal of elaborating the didactic material / object of learning, responds with the idea of a portable museum on the history of the neighborhood. The product was designed in a way that allows students to learn History as History is done - that is, questioning, arguing and building new knowledge from specific problems, historicized and verified in different sources of research. This material model proposes to ensure that the children perceive the historical process being constructed from the actions of all people, who make decisions every day, stand before the events and participate in the construction of the social group in which they are inserted.